2022
DOI: 10.1371/journal.pntd.0010337
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 reinfections with BA.1 (Omicron) variant among fully vaccinated individuals in northeastern Brazil

Abstract: Background The first case of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection in Rio Grande do Norte, northeastern Brazil, was diagnosed on March 12, 2020; thereafter, multiple surges of infection occurred, similar to what was seen elsewhere. These surges were mostly due to SARS-CoV-2 mutations leading to emergence of variants of concern (VoC). The introduction of new VoCs in a population previously exposed to SARS-CoV-2 or after vaccination has been a challenge to understanding the kinet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…This increase in the number of cases in the state follows what was observed in the rest of the country in the same period 32 . The high prevalence of the BA.1 lineage in genomes sequenced in the country is explained by the fact that this lineage is strongly associated with cases of infection and reinfection in vaccinated individuals 33 …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This increase in the number of cases in the state follows what was observed in the rest of the country in the same period 32 . The high prevalence of the BA.1 lineage in genomes sequenced in the country is explained by the fact that this lineage is strongly associated with cases of infection and reinfection in vaccinated individuals 33 …”
Section: Discussionsupporting
confidence: 71%
“…32 The high prevalence of the BA.1 lineage in genomes sequenced in the country is explained by the fact that this lineage is strongly associated with cases of infection and reinfection in vaccinated individuals. 33 Ai et al 34 June and July from 2022 respectively. Study conducted in South Africa in 2022, demonstrated that the BA.4 and BA.5 lineages emerged approximately 4 months after the onset of the wave of COVID-19 cases caused by the BA.1 strain in the country.…”
Section: Discussionmentioning
confidence: 99%
“…During COVID-19 the first three years of the COVID19 pandemic, the SARS-CoV-2 mutated and evolved with genetic variation in the population of circulating viral strains and after over 48 months of circulation within the human population it continues to mutate. The emergence of more recent SARS-CoV-2 variants, characterized by heightened transmissibility, raises concerns regarding their potential to compromise the protective effects of adaptive immunity elicited through natural infection or vaccination, since apparently immunity to either cases may be short lived (19), as we have observed here previously. Nevertheless, it is important to note that previous immunity, whether acquired through prior infection or vaccination, continues to demonstrate its association with protection against COVID-19 severity (55).…”
Section: Discussionmentioning
confidence: 56%
“…Intriguingly, SARS-CoV-2 variants had a significant impact on the number of cases and deaths in different parts of the globe, as seen when the Gamma variant emerged in South America (13)(14)(15) and the Delta and its sublineages in other parts of the globe (16,17). Those variants had distinct pathogenesis because of immune escaping from prior immunity generated through natural infection and/or vaccination (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…A second scenario could be the introduction of new viral quasi-species by a second and independent infection event which could explain the burst of mutations from day 1 to day 37. Previous studies have shown that reinfections occurred mostly by viruses from different genomic lineages, although reinfection can occasionally occur by viruses from the same genomic lineage [ 23 , 24 ].…”
Section: Case Presentationmentioning
confidence: 99%